Assessing Event Volunteer Motivational Factors and Quality of Life among University Students - Mohd Rashid, Norhidayah; Ma’amor, Hairunnisa; Zamzuri, Norol Hamiza; Ramli, Nurakmal; Ghazali, Ayu Rohaidah; Saridan, Shazril (Information Management and Business Review, 2023)
Volunteerism is a selfless and altruistic act of individuals dedicating their time, skills, and resources to support various causes and organizations without financial compensation. Hence, this paper aims to propose a conceptual framework for event volunteer motivation among university students and its impact on quality of life. Motivational factors measured by the volunteer motivational scale were proposed as independent variables, and quality of life as the dependent variable. This variable will regress to identify the relationship between quality of life among university students. The motivation to engage in volunteer work significantly impacts an individual’s quality of life. However, few studies have been conducted on the impact of volunteering activities on quality of life. Therefore, this study aims to develop a quality of life framework by considering event volunteer’s motivation as independent variables. This study will take place at Universiti Teknologi MARA (UiTM), Puncak Alam Campus whereby students from this university who already experience becoming volunteers will be involved as respondents. It is hoped that the contingency model of sports event volunteer motivation that is developed through this study will contribute to a better understanding of volunteerism and quality of life among students in higher institutions. Encouraging volunteering activities will educate youths to become responsible citizens by practicing a positive quality of life.